2020
DOI: 10.1101/2020.02.04.934562
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A new mechanism for a familiar mutation – bovineDGAT1K232A modulates gene expression through multi-junction exon splice enhancement

Abstract: The DGAT1 gene encodes an enzyme responsible for catalysing the terminal reaction in mammary triglyceride synthesis, and underpins a well-known pleiotropic quantitative trait locus (QTL) with a large influence on milk composition phenotypes. Since first described over 15 years ago, a protein-coding variant K232A has been assumed as the causative variant underlying these effects, following in-vitro studies that demonstrated differing levels of triglyceride synthesis between the two protein isoforms. In the curr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Based on the strongest statistical evidence from both GSOR and SMR for major traits of dairy cattle (non-linear assessment traits), we found that some traditionally recognised large-effect “single-gene” loci actually contain several adjacent genes or underlying spliced introns potentially causally linked to complex traits (Table 1 and Supplementary Data 1). We confirm the regulatory effects on milk production, gestation length, and height of several known causal loci, including DGAT1 10 via both gene expression and splicing, MGST1 25,28 and MATN3 29 via gene expression, and CSF2RB 30,31 and MUC1 32 via splicing. However, importantly, our evidence supports multiple regulatory loci underlying these major QTL.…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…Based on the strongest statistical evidence from both GSOR and SMR for major traits of dairy cattle (non-linear assessment traits), we found that some traditionally recognised large-effect “single-gene” loci actually contain several adjacent genes or underlying spliced introns potentially causally linked to complex traits (Table 1 and Supplementary Data 1). We confirm the regulatory effects on milk production, gestation length, and height of several known causal loci, including DGAT1 10 via both gene expression and splicing, MGST1 25,28 and MATN3 29 via gene expression, and CSF2RB 30,31 and MUC1 32 via splicing. However, importantly, our evidence supports multiple regulatory loci underlying these major QTL.…”
Section: Resultssupporting
confidence: 72%
“…In animals, only a few causal QTL are identified and one of the most extraordinary QTL is a mutation in the gene for diacylglycerol O-acyltransferase 1 (DGAT1) in cattle. This single QTL explains 30%-40% of the phenotypic variance of milk production traits 9,10 . While this QTL was previously identified to be caused by a protein-coding mutation 9,11,12 , more recent studies indicated regulatory effects 10,13 , possibly due to multiple causal mutations.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Iterations are defined relative to the base GWAS, with the base GWAS represented as iteration 0. N of hits: number of wavenumbers for which the variant was selected as the representative (most significant) tag variant for a peak may be due in part to an expression-based mechanism [64]. For the effects observed in the ABCG2, PAEP and DGAT1 genes, the p-values for the most significant FT-MIR wavenumber were always more significant than the comparable values for any of the milk composition traits.…”
Section: Multiple Ft-mir Wavenumber Qtl Observedmentioning
confidence: 99%
“…Additionally, a few thousand variants affecting the concentration of milk fat metabolites, i.e., metabolic mQTLs, also had significantly higher variance than SNPs in the 50k panel for cattle traits. Millions of variants that change gene expression levels (geQTLs) or RNA splicing (sQTLs) are also enriched with complex trait QTL (Xiang et al, 2018, Li et al, 2016, Silva et al, 2020, Fink et al, 2020, Lopdell et al, 2017). However, recent studies showed that variants close to genes with high or specific expression patterns had limited improvement in prediction accuracy (Fang et al, 2020, de Las Heras-Saldana et al, 2020).…”
Section: Introductionmentioning
confidence: 99%